Preterm Neonates with Respiratory Distress Syndrome: Ventilator-Induced Lung Injury and Oxidative Stress - Clarissa Gutiérrez Carvalho; Renato Soibelmann Procianoy; Eurico Camargo Neto; Rita C. Silveira (Journal of Immunology Research)
Ventilator-induced lung injury is well recognized, and appropriate arterial saturation target is unknown, so gentle modes of ventilation and minimizing oxidative stress have been well studied. Our objective was to analyze any association between the oxygen levels at blood sampling and plasma levels of the interleukins IL-6, IL-1β, IL-10, and IL-8 and TNF-α in preterm newborns under mechanical ventilation (MV) in their first two days. Methods. Prospective cohort including neonates with severe respiratory distress. Blood samples were collected right before and 2 hours after invasive MV. For analysis purposes, newborns were separated according to oxygen requirement: low oxygen (≤30%) and high oxygen (>30%) groups. Interleukins were measured using a commercially available kit. Results. 20 neonates (gestational age 32.2 ± 3 weeks) were evaluated. Median O2 saturation levels pre-MV were not different in both oxygen groups. In the high oxygen group, IL-6, IL-8, and TNF-α plasma levels increased significantly after two hours under MV. Conclusions. Despite the small sample studied, data showed that there is a relationship between VILI, proinflammatory cytokines, and oxygen-induced lung injury, but a study considering oxidative marker measurements is needed. It seems that less oxygen may keep safer saturation targets playing a less harmful role.